Trust and Risk: Evidence from Rural Banks in Emerging Market - Irwan Trinugroho; Aldy Fariz Achsanta; Taufiq Arifin; Nugroho Saputro (Faculty of Economic and Business, 2024)
Research Originality: This research is the first to discuss how rural bank risk-taking behaviour is affected by trust in particular when the poverty rate is high.Research Objectives: This research aims to investigate how risk in rural banks is shaped by the two dimensions of trust by taking into account different poverty levels across the regionResearch Methods: To thoroughly conduct our research, we use quarterly dataset of rural banks obtained from Otoritas Jasa Keuangan (OJK) for the period of 2010Q2 to 2016Q3 when the bail-out regime was still in effect. We employ a random effect model to account for individual heterogeneity.Empirical Result: Our evidence suggests that in-group trust is detrimental to rural banks’ risk. Conversely, out-group trust positively affects rural banks’ stability only if the region has a lower poverty level.Implications: To reduce risk, the rural bank has to use social capital and penetrate informally to the market where in-group trust is high to be able to compete with informal lending and to contribute better to society.JEL Classification: G21, G28, G32How to Cite:Trinugroho, I., Achsanta, A. F., Arifin, T., & Saputro, N. (2024). Trust and Risk Evidence from Rural Banks in Emerging Markets. Etikonomi, 23(2), 287 – 298. https://doi.org/10.15408/etk.v23i2.35775